Praktikum Berbasis Lingkungan pada Materi Larutan dapat Meningkatkan Motivasi dan Hasil Belajar Siswa - Kun, Suin (SCAD Independent, 2023)
The practicum method is one form of process skills approach. For high school students, practicums not only train how to use the right tools and materials, but also help their understanding of the chemistry material taught in class. Lack of tools and chemicals is often an obstacle to not conducting practicums. This study is a classroom action research that aims to determine the increase in student motivation and learning outcomes through the practicum method using materials from the environment on the solution material in class XI of SMA Negeri 9 Pontianak. The subjects of this study were 28 students consisting of 9 boys and 19 girls. The study was conducted in three cycles, and each cycle consisted of planning, implementation, evaluation, and reflection. The teaching process was carried out through practicums, discussions, presentations, and homework. The results of the study showed that there was an increase in student motivation and learning outcomes from cycle to cycle. Student learning outcomes in the cognitive aspect were ≥ 75.00 in cycle I at 57.2%, cycle II 85.7%, and cycle III 92.9%. The psychomotor aspect value was ≥ 75.00 in cycle I at 75%, cycle II 89.3%, and cycle III 96.4%